Assessing the Performance of the De Novo Postoperative Stress Urinary Incontinence Calculator. Issue 1 (January 2021) - Ross, James H.; Carter-Brooks, Charelle M.; Ruppert, Kristine M.; Giugale, Lauren E.; Shepherd, Jonathan P.; Zyczynski, Halina M.
Abstract : Objective: The aim of the study was to determine the performance of a previously published stress urinary incontinence (SUI) risk calculator in women undergoing minimally invasive or transvaginal apical suspensions. Methods: Using a database of stress-continent women who underwent minimally invasive or transvaginal apical suspensions, we calculated 2 prediction risks for development of SUI within 12 months based on inclusion of a "prophylactic" midurethral sling at the time of prolapse surgery. Observed subjective and objective continence status was abstracted from medical records. Regression models were created for the outcome of de novo SUI to generate receiver operating curves. Concordance ( c ) indices were estimated for the overall and procedure subgroups to determine the calculator's ability to discriminate between SUI outcomes. Results: Analyses included 502 women. De novo SUI was observed in 23.5% of women. The mean ± SD calculated risk of de novo SUI if a sling was performed was 18.9% ± 13.9 at 12 months compared with 36.4% ± 8.3 without sling. The calculator's discriminative ability for those with a planned sling was moderate ( c -index = 0.55, P = 0.037). The calculator failed to discriminate continence outcomes when a sling was not planned in the overall group ( c -index = 0.50, P = 0.799) and individual apical procedures. Conclusions: The SUI risk calculator is significantly limited in its ability to predict de novo SUI in our population of women planning minimally invasive apical suspensions. Refinements to the calculator model are needed to improve its utility in clinical practice.